Contribución al conocimiento sobre la Taxonomía, distribución geográfica y ecología de la Tortuga "Bache" (Chelydra Serpentina Acutirostris) Contribución al conocimiento sobre la Taxonomía, distribución geográfica y ecología de la Tortuga "Bache" (Chelydra Serpentina Acutirostris) - Medem Federico (Caldasia)
1. Studies on the external morphological characters of Chelydra serpentina acutirostris are presented, the principal scope of which contributes to the knowledge about the taxonomic status of this form considered as a valid subspecies. 2. These characteristics are compared with those of the other three subspecies, principally with Chelydra serpentina rossignonii. 3. Based on 18 specimens of acutirostris, mainly from Colombia, and 16 of rossignonii, mainly from Honduras, certain characters are re-evaluated. 4. The type specimens of the four living representatives of the genus Chelydra, commonly known as "Snapping Turtles", are as follows: a) Chelydra serpentina serpentina (Linnaeus), 1758. Holotype: Originally deposited at the Museum Adolphi Friderici Regis (Museum Drottningholmense), according to the Prodromus Stockholm, 1764, tom. II, p. 16, but presently lost (fide Andersson, 1900, pp. 4, 23). b) Chelydra serpentina acutirostris Peters, 1962. Holotype: ZBM 4500, hatchling, vicinity of Guayaquil, Ecuador, Carl Reiss. c) Chelydra serpentina rossignonii (Bocourt), 1868. Syntypes: MNHNP 1501, 1501 A, hatchlings, swamp of Panzos, vicinity of Rio Polochic, Guatemala, and MNHNP 1230, hatchling, Mexico, without exact locality, datum and collectors. d) Chelydra serpentina osceola Stejneger, 1918. Holotype: USNM 10369, Clearwater, Pinellas County, Florida, United States, September, 1879, S. T. Walker. 5. A redescription of the holotype of acutirostris is presented, and comparisons with the syntypes of rossignonii made. 6. Unfortunately, either the holotype or the syntypes all were described from hatchlings, many of the external morphological characters of which are markedly different from those of adults. 7. Certain external characters which are traditionally considered as constant in the keys of classification, although in reality they are not, but rather show a considerable variation, therefore they are of no taxonomic value in relation to an exact subspecific classification. 8. It is proposed to change the text of the existing keys as follows: a) Chelydra serpentina acutirostris. Length of anterior and lateral marginal shields equal to width in juveniles, markedly greater than width in subadults and adults; epidermal protuberances of nucal-cervical region few and short, rounded and blunt; sub-mandibular barbels from a single to three pairs (2.6 barbels) ; gular shield divided; bridge covered by three infra-marginal shields in almost all specimens; snout narrow and pointed, extends markedly over the tip of mandible. b) Chelydra serpentina rossignonii. Length of anterior and lateral marginal shields greater than width in adults and juveniles; epidermal protuberances of nucal-cervical region abundant and large, flat and pointed; sub-mandibular barbels in two pairs (4 barbels) in most specimens; gular shield divided; bridge covered by three infra-marginal shields in virtually all specimens;  snout narrow and pointed, extends markedly over tip of mandible. 9. As shown, there is only one easily discernible external character for distinguishing acutirostris from rossignonii: The configuration of the epidermal nucal-cervical protuberances. The relation between the length and width of the marginals -not constant in acutirostris, but constant in rossignonii- may also serve to a certain degree for distinction; however, they are not easily discernible since the corresponding measurements of each shield have to be taken. 10. Chelydra serpentina serpentina and serpentina osceola differ to a certain extent from acutirostris and rossignonii by configuration of snout, length of bridge, number of infra-marginals, and the presence of an entire gular shield in most specimens. 11. The epidermal protuberances are short, rounded and blunt in serpentina, but large, flat and pointed in osceola (first mentioned by Richmond, 1958, p. 42). 12. The validity of the taxonomic status is discussed. Boulenger (1902) and Vaillant (1911) did not accept acutirostris as a valid subspecies because the name was "not accompanied by an adequate description", and therefore used the name of rossignonii. The description given by Peters (op. cit., p. 627) is certainly not adequate; possibly he considered acutirostris as a mere variety since he wrote: "Chelydra serpentina var. acutirostris", Carr (1952, p. 71) considered osceola as "a weakly differenciated subspecies"; in contrast, Richmond (op. cit., p. 43) even took it for a valid species on the base of comparative anatomical studies. 13. We prefer to agree with Carr, and think that it would be more realistic to consider the four forms of the genus Chelydra as local populations ("demes") rather than as good subspecies, in accordance to our present and still scattered knowledge. 14. The following data on the ecology and geographical distribution are given: 15. The habitat of acutirostris consists of quiet waters, such as swamps, marshes, ponds and lagoons; it also lives in the headwaters of rivers and creeks either in the tropical rain forests or in the open valleys (which certainly were covered by abundant gallery forests in past times). 16. No sexual dimorphism exists, but the ♂♂ grow larger than the ♀♀. 17. From observations made of specimens kept in captivity, periods of sexual activity take place in June, July and November. 18. The egg-laying season takes place in February in the area of lower Río Atrato (Chocó); data from other regions are unknown. 19. About 27 - 30 either spherical or slightly ovoid hard-shelled eggs are laid in excavations made by the ♀ close to the waters. They measure between 3.5-3.3 and 3.9-3.2 centimeters; the weight was not taken. 20. The geographical distribution of acutirostris ranges from Costa Rica, Panama and Colombia into north-western Ecuador; the approximate limit to the south comprises the Guayas River System. 21. The exact limits of distribution -if any- of either acutirostris or rossignonii in Central America are unknown; as is true for osceola and serpentina in northern Florida (Carr, op. cit.), an overlapping zone possibly exists somewhere in Nicaragua or Costa Rica. 22. In Colombia, acutirostris -locally known as "la bache"- is to be found within the following areas: a) Along the Pacific coast between Bahía de Solano (Chocó] and Río Mataje (Nariño) which latter forms the border with Ecuador. b) In the Cauca Valley proper (Cauca and Valle). c) In the region of Armenia (Quindío) into which it evidently migrated from the Cauca Valley. Its migration into the Magdalena River System is blocked either by the Cañón del Cauca, a gorge situated between the Cordillera Occidental and Central, or by the western slopes of the Quindío Mountains which belong to the Cordillera Central. d) On the Atlantic sector of the Chocó, between Caño Negro, Río Tanela, lower Río Atrato and its tributary, Río Truandó, as well as Río Nercua, an affluent of the latter. Its presence on the middle and upper reaches of the Atrato is not proved but can be suspected. e) On the upper Rio Sinú (Córdoba), between Caño Juí in the vicinity of the village Tierralta and Río Manso, the uppermost tributary of the Sinú. 23. No studies exist about its presence between the eastern shore of the Gulf of Urabá or Darién and Rio Sinú, but certainly it once migrated from the Chocó into the latter. 24. The center of evolution of the genus Chelydra apparently was situated in the United States, from where the migration took place during the Terciary. Fossils are known from the Pleistocene of the United States (Carr, op. cit.), but no fossil material was described from Colombia until now. 25. Many more studies, carried out with large series of adults of both sexes, juveniles, and especially with living specimens, are badly needed in order to clarify the still remaining problems concerning the taxonomy, ecology and geographical distribution of acutirostris and rossignonii. 1º Se presenta un estudio sobre Chelydra serpentina acutirostris, dando énfasis a las características morfológicas externas, con el fin de contribuir al conocimiento sobre el estado taxonómico de esta subespecie. 2º Se compara estas características con las de las demás subespecies del género Chelydra, y especialmente con Chelydra serpentina rossignonii, procedente de la América Central. 3º Se hace una redescripción del holótipo de acutirostris (ZMB 4500) en comparación con los tres síntipos de rossignonii (MNHNP 1501, MNHNP 1501 A y MNHNP 1230). 4º Resulta que tanto el holótipo como los síntipos han sido descritos a base de ejemplares recién nacidos, muchas de las características morfológicas externas son diferentes de las de los adultos. 5º A base de 18 ejemplares de acutirostris, procedentes en su gran mayoría de Colombia, y 16 de rossignonii, procedentes principalmente de Honduras, ciertos caracteres externos son críticamente evaluados. 6º En acutirostris, el número de las bárbulas submandibulares varía entre uno solo y tres (3) pares, es decir, de 2 a 6 bárbulas individuales. 7º En cambio, la gran mayoría de los ejemplares de rossignonii tiene dos (2) pares de bárbulas, es decir, 4 individuales, 8º Las protuberancias epidermales situadas en la región nucal-cervical son pocas, redondeadas y romas en acutirostris; en cambio, abundantes, planas y puntiagudas en rossignonii. 9º El número de las placas inframarginales del puente, el cual conecta el plastron con el carapax, son tres (3) en la mayoría de los ejemplares, tanto en acutirostris como en rossignonii. 10. Comparando las otras dos subespecies, procedentes de los Estados Unidos, las protuberancias epidermales nucal-cervicales son redondeadas y romas en Chelydra serpentina serpentina, y planas y puntiagudas en Chelydra serpentina osceola. 11. El puente en serpentine y osceola es más corto que en acutirostris y rossignonii, y está cubierto por dos placas inframarginales solamente en la gran mayoría de los especímenes. 12. En todos los ejemplares de acutirostris y rossignonii se encontraron dos (2) placas gulares; en cambio la mayoría de los especímenes de serpentina y osceola tiene la placa gular entera. 13. No se encontro una diferencia perceptible respecto a la forma de la cabeza y, especialmente, del hocico de acutirostris y rossignonii; es puntiagudo y sobresaliente en ambas; en cambio el hocico de serpentina y osceola es más corto y romo que en las dos subespecies tropicales, aún en los juveniles. 14. Las escamas salientes y encrestadas, situadas en tres (3) hileras en la cola, varían individualmente respecto a su forma y cantidad; no representan ningún carácter subespecífico para distinguir acutirostris de rossignonii. 15. Las relaciones entre la longitud y el ancho de las placas marginales que bordean el carapax, tampoco tienen caracteres constantes en acutirostris es igual al ancho en los juveniles pero notablemente mayor que el ancho en los adultos. 16. En cambio, la longitud de las marginales es mayor que el ancho en los juveniles y adultos de rossignonii. 17. Se discute el estado taxonómico de las cuatro (4) formas del género Chelydra, con énfasis en acutirostris. Tanto Boulenger (1902) como Vaillant (1911) consideraron ésta como una subespecie no válida por "no estar acompañada por una descripción adecuada", y usaron el nombre de rossignonii.  Igualmente, Carr (1952 consideró a osceola como "una subespecie débilmente definida", mientras Richmond (1958), a base de estudios anatómicos comparados, está convencido que representa no solamente una subespecie sino una especie válida. 18. Estamos de acuerdo con Carr, por razón de que la mayoría de los caracteres, considerados como constantes y por eso de valor taxonómico, no lo son. Para distinguir acutirostris de rossignonii existe un solo carácter morfológico externo fácilmente discernible: la configuración de las protuberancias epidermales nucal-cervicales.  El número de las bárbulas submandibulares es muy variable en acutirostris pero más constante en rossignonii, mientras la relación entre la longitud y el ancho de las marginales es constante en rossignonii pero no en acutirostris; además, no es fácilmente discernible, sino hay que tomar las dimensiones correspondientes. 19. se propone un cambio del texto de las claves de determinación taxonómica para acutirostris y rossignonii. 20. Se llega a la conclusión que las cuatro (4) formas de Chelydra no representan subespecies bien definidas, sino más bien populaciones locales ("demes") . 21. El habitat de acutirostris consiste en las aguas mansas; su nicho ecológico, sin embargo, no está estrechamente restringido. Vive tanto en las lagunas, pozos y cabeceras de los caños dentro del habitat denominado como "selva tropical pluvial", como en los inmensos esteros de la costa del Pacífico y en los lagos y remansos de los valles abiertos (los cuales, posibleme han sido cubiertos parcialmente por bosques en los tiempos pasados. 22. No existe un dimorfismo sexual discernible, en contraste con la mayoría de las demás Testudines; sin embargo, los ♂♂ crecen más grandes que las ♀♀. 23. La época de celo se efectúa en junio, julio y noviembre, según las observaciones hechas con ejemplares mantenidos en cautividad. 24. El período de anidación se efectúa en febrero en el bajo Atrato (Chocó); faltan los datos correspondientes de las demás regiones. 25. Se encontraron hasta 27 huevos de forma circular o ligeramente ovaloide; miden de 3.5 - 3.3 cm a 3.9 - 3.2 cm. No se tomó el peso. 26. La distribución geográfica de Chelydra serpentina acutirostris abarca el área entre Costa Rica, Panamá, Colombia y el Ecuador. El limite aproximado hacia el sur es la hoya del río Guayas, que desemboca en la bahia de Guayaquil. 27. En Colombia se encuentra en las siguientes areas: a) La costa del Pacífico, desde el río Valle (Chocó) hasta el río Mataje (Nariño), situado en la frontera entre Colombia y Ecuador. b) El Valle del Cauca propiamente dicho. c) La region de Armenia (Quindío). Su migración hacia la hoya del Magdalena está inhibida por dos (2) barreras naturales: el cañón del Cauca y la vertiente occidental del Quindío. d) En la región occidental del golfo de Urabá (Chocó) y en el bajo Atrato y sus afluentes. e) En el alto Sinú (Córdoba), desde el caño Juí hasta el río Manso. 28. El género Chelydra tenía su centro de evolución en el norte, de donde ha migrado hacia el sur durante el período del Terciario.  Fósiles de acutirostris, procedentes de Colombia, son todavía desconocidos.